DESIGN OF AUTOMATIC WATER FAUCET FOR A READY FOOD RESTAURANT SINK USING MICROCONTROLLER BASED ULTRASONIC SENSOR - Asri; Akmal Sujudi; Andik Bintoro; Habib Muharry Yusdartono; Ezwarsyah (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
Technological developments in the field of control are increasingly advanced, especially in the world of electronics. Electronic water faucets are one example that we can find in fast food restaurants which are quite expensive for some groups and water is often wasted when the hand washing process is in progress. Therefore this research was carried out by designing and building an automatic faucet in a sink so that there is no wastage of water. The problems faced are the use of manual faucets that are not sterile and the process in the field when washing hands is not efficient and hygienic. The method used is to design and build mechanical and electronic components based on microcontrollers. By utilizing Arduino UNO, HC-SR04, L298N, Relay and DC pump, hand washing sink will facilitate the hand washing process. The design of an automatic water faucet for a fast food restaurant sink based on a microcontroller was successfully realized and implemented with the realization that water managed to come out of a 12V DC pump capable of dispensing water according to the reach of the hand between 2.5cm to 27.5cm which was carried out by the HC-SR04 sensor. The process carried out is that the automatic water faucet at the sink in a fast food restaurant can simplify the hand washing process and reduce water wastage with a water saving of 5.3 liters for adults and 8.66 liters for small children. The average water used by adults for automatic sinks is 0.49 Ɩiter/person and young children is 0.45 Ɩiter/person, with a water velocity of 0.163 Ɩ /s for adults and 0.150 Ɩ /s for small children.